Global experience of science and technology clusterization in the digital epoch: intellectual and patent activities within economic sectors - Краус, К. М.; Kraus, K. M. (Видавництво Львівської політехніки, 2024)
Сучасна кластерна парадигма економічного розвитку має на меті сприяти поглибленню зв’язків між ринками капіталу та передовими ІКТ і цифровими технологіями, розвитком економіки знань та екологічністю виробництва, соціальною спрямованістю технологій, отримання синергетичних ефектів від спільних науково-дослідних розробок. GII 2023 засвідчив першість у рейтингу науково-технологічних кластерів світу за економічними результатами кластерів Азійського регіону, однак рейтинг науково-технологічних кластерів за інтенсивністю не підтверджує прямої залежності між щільністю населення на певній території чи в певному місті та економічними результатами кластеру. Результатом дослідження став виявлений факт того, що сфера наукових інтересів винахідників та дослідників кластерів сьогодні розширюється так само швидко, як і потреби людей, а тому патентна активність простежується в біо- та медичних технологіях, фармацевтиці та оптиці, інформаційних, цифрових, комп’ютерних та аудіовізу- альних технологіях, що цілком виправдано в еру цифровізації та інформатизації як економіки, так і суспільства. Запропоновано низку пріоритетних напрямів посилення науково-технологічної кластеризації в розвинених країнах світу та окреслено їх очікувані практичні результати.

Purpose – The purpose of this study is to carry out a comparative analysis of economic results and innovative activity within the scientific and technological clusters of the world, to establish the relationship between the population density of a certain agglomeration and the productivity of its inventors, the effectiveness of researchers and business efficiency, to evaluate the impact of digital technologies on economic success science and technology cluster. Design/methodology/approach – In the article, the author used the method of analysis to study the scientific literature that sheds light on the understanding of the phenomenon of the science and technology cluster, and the method of abstraction helped to separate the economic results of the activity of scientific and technological clusters from their environment. The formulation of conclusions regarding the patterns of development of modern world leaders among science and technology clusters was implemented using the methods of synthesis and generalization, and the comparison of researchers’ views on the priority of cluster activity in the economy was carried out using the method of comparison. The statistical method helped the author establish cause-and-effect relationships in the activity of science and technology clusters in the aspect of general development, and the graphic method provided visualization of the state of development of modern science and technology clusters in the world. Findings – The modern cluster paradigm of economic development aims to promote the deepening of connections between capital markets and advanced ICT and digital technologies, the development of the knowledge economy and environmental sustainability of production, the social orientation of technologies, and obtaining synergistic effects from joint scientific and research developments. The Global Innovation Index 2023 proved the first place in the rating of the world’s science and technology clusters by the economic results of clusters in the Asian region, however, the rating of science and technology clusters by intensity (relative to population density) does not confirm a direct relationship between the population density in a certain territory or in a certain city and economic results cluster. The result of the research was the revealed fact that the field of scientific interests of inventors and researchers of clusters today is expanding as fast as the needs of people, and therefore patent activity can be traced in bio- and medical technologies, pharmaceuticals and optics, information, digital, computer and audiovisual technologies, which is fully justified in the era of digitization and informatization of both the economy and society. Practical implications – The results of this research are of practical interest to everyone who is a direct participant in the science and technology cluster (scientists, economists, inventors, programmers, educators, officials, businessmen, etc.) and who is tangential to its activities, because they all get the opportunity to work on the principles mutual assistance for the sake of common goals, stimulated the development of local markets, scaled up their activities, promoted economic growth. Originality/value – The presented study covers both scientific and real economic results in terms of cluster activity of Japan, the Republic of Korea, the USA, China and other countries of the world, which allows focusing attention on the social behavior and mentality of the people of a certain country, economic and technological maturity, political will and institutional support contribute to the creation and development of science and technology clusters. The author proposes priority directions for strengthening scientific and technological clustering in the developed countries of the world, outlines the expected results from their practical implementation and determines the prerequisites for the beginning of their implementation.
Світовий досвід науково-технологічної кластеризації в цифрову епоху: інтелектуальна та патентна діяльність в розрізі галузей економіки
Keywords: науково-технологічний кластер; інноваційна діяльність; цифрові технології; цифровізація економіки; агломерація; регіональна спеціалізація; публікаційна актив- ність; патентна діяльність; мережевість зв’язків; science and technology cluster; innovative activity; digital technologies; digitalization of the economy; agglomeration; regional specialization; publishing activity; patent activity; networking of connections; F02; F20; O30; O32; O34; R12; 339.9; 330.3; 004); (347; 332.1